2015
DOI: 10.3727/096368913x676907
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein 9 and 13 Induce C3H10T1/2 Cell Differentiation to Cardiomyocyte-Like Cells in Vitro

Abstract: The present study aimed to evaluate the effect of bone morphogenetic protein 9 (BMP9) and BMP13 on cardiac differentiation of C3H10T1/2 cells in vitro and to characterize the differentiated cells on their ultrastructure and transmembrane electrophysiological features. C3H10T1/2 cells were transfected with the vectors for BMP9 or BMP13 and differentiated into cardiomyocytes in vitro for up to 28 days. The expression of cardiac-specific genes Gata4 and Mef2c and proteins troponin T (cTnT) and connexin 43 (Cx43) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…[25] Moreover, some cells of this group depicted cytoplasmic striations and disc-like structures which could be attributed to the expression of cardiac troponin and connexin proteins. [26] In addition, cells of subgroup IIc appeared elongated forming myotube-like structures with string-bead-like nuclei which could be due to the fusion of more primitive myoblasts. On the other hand, cells of subgroup IId regressed in size with no cytoplasmic striations in contrary to other researchers who reported that the cultured cells retained the cardiogenic phenotype until the 8 th week.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Moreover, some cells of this group depicted cytoplasmic striations and disc-like structures which could be attributed to the expression of cardiac troponin and connexin proteins. [26] In addition, cells of subgroup IIc appeared elongated forming myotube-like structures with string-bead-like nuclei which could be due to the fusion of more primitive myoblasts. On the other hand, cells of subgroup IId regressed in size with no cytoplasmic striations in contrary to other researchers who reported that the cultured cells retained the cardiogenic phenotype until the 8 th week.…”
Section: Discussionmentioning
confidence: 99%